Degenerate PCR Primers to Reveal the Diversity of Giant Viruses in Coastal Waters - Yanze Li (Viruses, 2018)
“Megaviridae” is a proposed family of giant viruses infecting unicellular eukaryotes. These viruses are ubiquitous in the sea and have impact on marine microbial community structure and dynamics through their lytic infection cycle. However, their diversity and biogeography have been poorly characterized due to the scarce detection of Megaviridae sequences in metagenomes, as well as the limitation of reference sequences used to design specific primers for this viral group. Here, we propose a set of 82 degenerated primers (referred to as MEGAPRIMER), targeting DNA polymerase genes (polBs) of Megaviridae. MEGAPRIMER was designed based on 921 Megaviridae polBs from sequenced genomes and metagenomes. By applying this primer set to environmental DNA meta-barcoding of a coastal seawater sample, we report 5595 non-singleton operational taxonomic units (OTUs) of Megaviridae at 97% nucleotide sequence identity. The majority of the OTUs were found to form diverse clades, which were phylogenetically distantly related to known viruses such as Mimivirus. The Megaviridae OTUs detected in this study outnumber the giant virus OTUs identified in previous individual studies by more than an order of magnitude. Hence, MEGAPRIMER represents a useful tool to study the diversity of Megaviridae at the population level in natural environments.